Delaying diagnostic procedure significantly increases mortality in patients with invasive mucormycosis. Issue 12 (December 2015) - Jeong, Su Jin; Lee, Ji Un; Song, Young Goo; Lee, Kyoung Hwa; Lee, Min Joo
Summary: Invasive mucormycosis is an uncommon but increasing life‐threatening fungal infection. The present study investigated clinical characteristics and mortality among patients diagnosed as invasive mucormycosis infection. We retrospectively reviewed a total of 24 histologically proven cases of invasive mucormycosis at two tertiary care referral hospitals between November 2005 and February 2014. Overall survival was 50% ( n  = 12). The time between onset of symptom and diagnostic procedure proved to be associated with mortality ( P  = 0.009). In addition, preexisting renal failure and thrombocytopenia demonstrated trends toward a poor outcome in our study ( P  = 0.089 and 0.065, respectively). On multivariate regression analysis, delayed diagnostic procedure (more than 16 days after the onset of symptoms) was an independent predictor of mortality (OR= 12.34, 95% CI, 1.43–10.64; P  = 0.022). Mucormycosis is a destructive fungal infection that is associated with high mortality rates, ranging from 40% to 100% depending on the form of disease. When a clinician suspects invasive mucormycosis infection, an early diagnostic procedure performed within 16 days from the onset of symptom and early initiation of antifungal therapy will lead to successful management of this highly fatal disease.